Nitric oxide and S‐nitrosoglutathione function additively during plant immunity. Issue 2 (24th February 2016) - Yun, Byung‐Wook; Skelly, Michael J.; Yin, Minghui; Yu, Manda; Mun, Bong‐Gyu; Lee, Sang‐Uk; Hussain, Adil; Spoel, Steven H.; Loake, Gary J.
Summary: Nitric oxide (NO) is emerging as a key regulator of diverse plant cellular processes. A major route for the transfer of NO bioactivity is S ‐nitrosylation, the addition of an NO moiety to a protein cysteine thiol forming an S ‐nitrosothiol (SNO). Total cellular levels of protein S ‐nitrosylation are controlled predominantly by S ‐nitrosoglutathione reductase 1 (GSNOR1) which turns over the natural NO donor, S ‐nitrosoglutathione (GSNO). In the absence of GSNOR1 function, GSNO accumulates, leading to dysregulation of total cellular S ‐nitrosylation. Here we show that endogenous NO accumulation in Arabidopsis, resulting from loss‐of‐function mutations in NO Overexpression 1 ( NOX1 ), led to disabled Resistance ( R ) gene‐mediated protection, basal resistance and defence against nonadapted pathogens. In nox1 plants both salicylic acid (SA) synthesis and signalling were suppressed, reducing SA‐dependent defence gene expression. Significantly, expression of a GSNOR1 transgene complemented the SNO‐dependent phenotypes of paraquat resistant 2‐1 (par2‐1 ) plants but not the NO‐related characters of the nox1‐1 line. Furthermore, atgsnor1‐3 nox1‐1 double mutants supported greater bacterial titres than either of the corresponding single mutants. Our findings imply that GSNO and NO, two pivotal redox signalling molecules, exhibit additive functions and, by extension, may have distinct or overlapping molecular targets during both immunity and development.